Antimicrobial Resistance and Molecular Identification of Clinical Multi-Drug Resistant Enterobacter Cloacae - Fajriah, Siti Nur; Inggraini, Maulin; Ilsan, Noor Andryan; Anindita, Reza (Universitas Islam Negeri Mataram, 2021)
Enterobacter cloacae is a Gram-negative bacteria causing nosocomial infections. This bacteria has increased resistance to various antibiotics in the past five years, resulting in a multi-drug-resistant (MDR) phenotype. In particular, MDR E. cloacae causes longer hospitalization time, increases medical costs, and affects morbidity and mortality. This study aimed to observe the minimum inhibitory concentration (MIC) of clinical E. cloacae towards several antibiotics and molecular identification of MDR E.cloacae. This study was conducted in a descriptive design. Secondary data was collected at the microbiology laboratory of the Teaching Hospital in Bekasi, Indonesia, from May to September 2020. Sampel was carbapenem resistant E.cloacae. The isolate was originated from a human clinical specimen, then was confirmed molecular identification using 16s rRNA. In this study, only one carbapenem-resistant E. cloacae, which is also MDR bacteria, was found. This E. cloacae was categorized as MDR bacteria since it was resistant to more than three antibiotic classes, including carbanemen, extended-spectrum cephalosporin, penicillins + β lactamase inhibitor, antipseudomonal penicillins + β lactamase inhibitor aminoglycoside, and penicillin. Vitek 2 identification of this isolate was E. cloacae complex. It showed similar results to molecular identification based on a partial sequence of 16s rRNA. BLASTn result of the trimmed sequence was E. cloacae with 99.78 % similarity.